On the influence of a layer of a viscous compressible fluid on the surface instability of the incompressible elastic half-plane exposed to finite initial deformations - Bagno, A.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The problem of propagation of harmonic waves in the pre-deformed incompressible elastic half-space that interacts with a layer of an viscous compressible fluid is considered. The study is based on the three-dimensional linearized equations of theory of elasticity of finite deformations for the incompressible elastic half-space and the three-dimensional linearized Navier—Stokes equations for a layer of a viscous compressible fluid. The approach based on the utilization of representations of general solutions of the linearized equations for an elastic solid and a fluid is applied. A dispersion equation, which describes propagation of harmonic waves in a hydroelastic system, is obtained. The dispersion curve for surface waves over a wide range of frequencies is constructed. The effects of finite initial deformations of the elastic half-space and of the thickness of the layer of a viscous compressible fluid on the phase velocities, attenuation coefficients, dispersion of the surface waves, and surface instability of a hydroelastic waveguide are analyzed. The numerical results are presented in the form of graphs, and their analysis is given.